2023
DOI: 10.21203/rs.3.rs-2367609/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and microbiological outcomes of subgingival instrumentation supplemented with high-dose omega-3 polyunsaturated fatty acids in periodontal treatment – a randomized clinical trial

Abstract: Purpose This study aimed to evaluate the impact of dietary supplementation with omega-3 polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) combined with scaling and root planning (SRP) in untreated periodontitis stage III and IV. Methods Forty patients were randomly assigned to test group receiving SRP plus omega-3 PUFAs (n = 20) and control group receiving SRP alone (n = 20). Clinical changes of pocket probing depths (PD), clinical attachment level (CAL), bleedin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
1
0
0
Order By: Relevance
“…A: RCS of omega-3; B: RCS of omega-6; C: RCS of omega-6/omega-3 fatty acids levels and periodontal parameters were consistent with the findings of most studies [28,29]. Stańdo-Retecka, M. et al reported that compared to patients in the control group, patients treated with omega-3 PUFA demonstrated significantly lower rates of bleeding on probing (BOP), greater AL gains, and an increased number of closed pockets at the three-month mark [30]. The anti-inflammatory, antibacterial, and inflammatory bone loss-regulating properties of omega-3 might be the primary mechanisms by which it regulates periodontitis [31][32][33].…”
Section: Discussionsupporting
confidence: 86%
“…A: RCS of omega-3; B: RCS of omega-6; C: RCS of omega-6/omega-3 fatty acids levels and periodontal parameters were consistent with the findings of most studies [28,29]. Stańdo-Retecka, M. et al reported that compared to patients in the control group, patients treated with omega-3 PUFA demonstrated significantly lower rates of bleeding on probing (BOP), greater AL gains, and an increased number of closed pockets at the three-month mark [30]. The anti-inflammatory, antibacterial, and inflammatory bone loss-regulating properties of omega-3 might be the primary mechanisms by which it regulates periodontitis [31][32][33].…”
Section: Discussionsupporting
confidence: 86%